The Effect of Legal Financial Obligations on Reentry Experiences - Pleggenkuhle, Breanne Rae (2012)
In 2010, over 700,000 offenders were released from prison (Guerino, Harrison, and Sabol, 2012), and on any given day over seven million individual are under some form of correctional supervision (Glaze, 2011). Research has documented the collateral consequences of transition such as diminished employment prospects and limited housing availability. Fiscal concerns have shifted some of the costs of prosecution and correctional supervision to the offender, resulting in accumulation of legal financial obligations. However, little research has examined of the effect of legal financial obligations on reentry outcomes. This study has two broad goals. The first objective was to document the prevalence and context of legal financial obligations among a contemporary sample of individuals under supervision in the community. Second, the effects of financial obligations on reentry are considered. Overall, most offenders have financial obligations and struggle with employment. Second, legal financial obligations produce additional barriers to reentry. Legal responsibilities can limit social mobility, negatively impact views of the criminal justice system, and increase stress and negative emotions. However, the effect of legal fees on recidivism is mixed. The work concludes with suggested policy modifications that may mitigate negative consequences of legal financial obligations